Estudo em galpões de concreto pré-moldados considerando a interação entre pórtico e alvenaria de vedação - Santos, Emerson de Souza dos (2019)
The constructions with framed structures formed by reinforced precast concrete elements are commonly seen in all Brazilian territory. They are high and slender structures that the wind action can cause elevated displacements, and at the most of situations full filled by masonry. In this context, the masonry inclusion on the framed system, using blocks of compressive strength up to 3.0 MPa could seem like an efficient way to the stiffen as a possibility to improve the structural system behavior. From another point of view, the excessive requested of the masonry could result in cracks appearing, which could be avoided by the use of a more resistant blocks. This study objectives to evaluate the masonry influence in the structural systems behavior of skeletal systems precast reinforced concrete, through the efforts and displacement value in the wall and column elements. The skeletal system is formed by five parallel frames connected to each other by transversal beams. The linear analysis is done by numerical simulations, considering the masonry contribution by means of a diagonal compression bar of fixed dimension (w). By using ABAQUS® software, three two-dimensional frames models were built to better understand the stresses distribution to the wall, such as the contact and compression region. For computational simulations of skeletal system, two computational modules were used in MATLAB language, namely: P3D and P3DGALPAO. The P3D module consists of a general program of linear analysis of three-dimensional frames in which connection perfectly rigid, semi-rigid and articulate are considered. The P3DGALPAO module corresponds to a customization of the general module P3D, in which a frame analysis template is created from a set of parameters. The results obtained for efforts and displacements were evaluated according to the criteria established by Brazilian Standards NBR 9062 (ABNT, 2017) and NBR 6118 (ABNT, 2014). Comparing the results of the analysis without equivalent diagonal and with this one, the diagonal promoted some advantages like the reduction of the flexural moments at the column base and the displacements at the top of the columns. It was verified that the masonry only suffered rupture by traction. Walls with blocks of 1.5 MPa withstand the stresses resulting from the incidence of wind in the structure with a maximum speed of 30 km/h. To prevent cracking, blocks with of 2.0 MPa or 3.0 MPa are recommended, which withstand the action of winds at speeds of 40 km/h and 50 km/h, respectively. The block with 3.0 MPa compression strength presented an adequate result, although it has a low resistance, indicating that it is possible an improvement in the stiffening of the lateral frames with the use of blocks of good quality and with larger .